Do Nonpartisan Programmatic Policies Have Partisan Electoral Effects? Evidence from Two Large-Scale Experiments. - Imai, Kosuke; King, Gary; Velasco Rivera, Carlos (Journal of Politics, 2020)
A vast literature demonstrates that voters around the world who benefit from government discretionary spending increase their electoral support for the incumbent party. But, contrary to theories of political accountability, some suggest that voters also reward incumbent parties for "programmatic" spending, over which incumbents have no discretion, even when passed with support from all major parties. Why voters would attribute responsibility when none exists is unclear, as is why minority parties would support legislation that costs them votes. We study two prominent programmatic policies. For the first, we design and implement one of the largest randomized social experiments ever. For the second, we reanalyze studies that came to opposite conclusions, using a large-scale randomized experiment and a natural experiment. By improving statistical methods and correcting data errors, we show that evidence from all analyses of both policies is consistent: programmatic policies have no measurable effect on voter support for incumbents.